An extension of the MOORA method for solving fuzzy decision making problems - Stanujkic, Dragisa (Technological and Economic Development of Economy, 2014)
The aim of this paper is to propose an extension of the MOORA method to use the triangular fuzzy numbers. In this paper, several methods for defuzzification and calculation of the distance between two fuzzy numbers, are discussed. By applying these methods, the Ratio system and the Reference point approach of the MOORA method can be used in fuzzy environment. Thanks to the proposed modification, the MOORA method can be used to solve a greater number of real world problems. To demonstrate the applicability and effectiveness of the proposed approach, an example of grinding circuits design selection is considered.